Sirolimus-Eluting Balloon for the Treatment of Coronary Lesions in Complex ACS Patients: The SELFIE Registry - Gianluca Caiazzo; Mario De Michele; Luca Golino; Vincenzo Manganiello; Luciano Fattore (Journal of Interventional Cardiology)
Background. Sirolimus-coated balloons (SCBs) represent a novel therapeutic option for both in-stent restenosis (ISR) and de novo coronary lesions treatment, especially in small vessels. Our registry sought to evaluate the procedural and clinical outcomes of such devices in a complex acute coronary syndrome (ACS) clinical setting. Methods and Results. We treated 74 consecutive patients with percutaneous coronary intervention (PCI) with at least 1 SCB used for ISR and/or de novo coronary lesion in small vessels at our institution. Sixty-two patients presented with ACS, and their data were included in our analysis. The mean age was 67 ± 10 years, and patients presenting with ST-elevated myocardial infarction (STEMI) were 14 (23%). De novo lesions were 52%, whereas ISR was 48%. Procedural success occurred in 100% of the cases. At the 11 ± 7 months follow-up, major adverse cardiovascular events (MACEs) were 3 (4.8%). Cardiovascular death (CD) occurred in 1 (1.6%) patient and myocardial infarction (MI) in 2 patients (3.2%) as well as ischemia-driven target lesion revascularization (TLR). One probable subacute thrombosis occurred (1.6%) with no major bleedings. In a subgroup analysis, the incidence of MACE did not show significant differences between patients treated for de novo lesions and ISR (HR: 0.239; CI 95%: 0.003–16.761, p=0.509). Conclusions. In the SELFIE prospective registry, SCB showed a good safety and efficacy profile for the treatment of coronary lesions, both ISR and/or de novo in small vessels, in a complex ACS population of patients at the 11 ± 7 months follow-up.